L’éducation au politique sur des questions socialement vives (QSV) liées au développement durable (DD) et aux objectifs de développement durable (ODD) - Alain Legardez; Maryse Cadet-Mieze; Agnieszka Jeziorski (Éducation et Socialisation)
To what extent the research work on socially acute questions (SAQs) may contribute to political education? Many authors interested in this topic are concerned with education for a political eco-citizenship from a transformative-critical perspective. We propose to illustrate these relationships by studying issues related to education for sustainable development (ESD), from a didactic perspective, and more specifically by the presentation-discussion of a collaborative training-action-research: the FECODD project (Training, Education and Skills and Sustainable Development Goals). How SD education - throughout the SDGs – may contribute to a better understanding and apprehension of the political issues that arise from it ?